Information technology needs and requirements of small and medium scale enterprises in Iloilo City and the level of information technology competency skills of graduating students in UPV-CM - Cabiten, Janetlyn M.; Garmino, Cyrene R.; Salido, Jay Roger P.; Somo, Christine Anne C.
Information Technology is very important in the work and personal lives of every individual. Even students have a basic understanding in IT and the proper application skill since it is a primary requirement in the workplace nowadays. Cognizant to the IT qualifications of business establishments in the workforce and how UPV-CM as an academic institution prepares and train the students in different aspects of IT, the group investigated " Information Technology Needs and Requirements of Small and Medium Scale Enterprises in Iloilo City and the Level of Information Technology Competence of Graduating students in UPV-CM." For this study the researchers have thirty (30) graduating students from UPV-CM as its respondents. From the thirty (30) graduating students, ten (10) of these were selected from the BS Accountancy and the same respective number of students will be drawn from BS Marketing and BS Management. The researchers also surveyed twelve (12) enterprises for this study mainly from the bank sector as respondents, and half of where drawn from small enterprises and the other half from the medium scale enterprises. The same goes with the Service sector. The group decided to study the respondents that are graduating students in UPV- CM and Small and Medium Scale Enterprises here in Iloilo City to compare the competency skills of students in terms of the IT qualifications being demanded by the business establishments. The researchers therefore concluded that the level of IT aptitude skills of graduating students in UPV-CM is competent enough to meet the standards of the Small and Medium Scale enterprises he re in Iloilo City. The researcher recommends further analysis and investigation.